Performance of broilers fed graded levels of bio- detheobrominized cocoa bean shell (cbs) based diets (2014)
A study was carried out to observe the effect of bio-detheobromised cocoa bean shell based diets on the performance of broilers. One hundred and ninety six (196) day-old broiler chicks were randomly assigned to seven diets, with each diet replicated four times and seven birds allocated to each, replicate. Cocoa Bean Shell was included at varying levels of 0, 5, 10, 15, 20, 25 and 30% in the diets. Results showed that Cocoa Bean Shell inclusion had significant influence on the final weight, weight gain, feed intake and feed conversion ratio (p<0.05), while there were no significant differences observed (p>0.05) for gut weight and primal cuts. It was observed that Cocoa Bean Shell inclusion at up to 10% had no adverse effect on the performance and primal cut output of broilers.